Contribution of autochthonous yeasts with probiotic potential to the aroma profile of fermented Guajillo pepper sauce - Lara‐Hidalgo, Carlos; Belloch, Carmela; Dorantes‐Alvarez, Lidia; Flores, Mónica (Journal of the science of food and agriculture, 2020)
BACKGROUND Three yeast strains with probiotic potential, Hanseniaspora opuntiae, Pichia kudriavzevii, and Wickerhamomyces anomalus were inoculated in the fermentation of Guajillo chilli pepper (Capsicum annuum L.) sauce, and the different aroma profiles were investigated. Using headspace solid‐phase microextraction‐gas chromatography‐mass spectrometry (HS‐SPME‐GC‐MS) analysis and gas chromatography‐olfactometry (GCO), flavour compound production was evaluated during the fermentation of the Guajillo chilli pepper sauces. RESULTS A total of 78 volatile compounds were identified during the yeast fermentation of the sauce. Most aldehydes and terpenes detected were present at the beginning of the fermentation, indicating a Guajillo chilli pepper origin. Among the 34 active aroma compounds detected by GCO, propanoic acid (cheesy), 3‐methylbutanoic acid (sharp, cheese), ethyl 2‐methylbutanoate (fruity), and 6‐methyl‐5‐hepten‐2‐one (strong, citrus) were identified as key aroma contributors produced by the inoculation of the yeasts. A different aroma profile was produced by probiotic yeast. Hanseniaspora opuntiae produced an aroma profile with herbal and green notes based on high production of aldehydes, ketones, and acetic acid. Pichia kudriavzevii and W. anomalus produced fruity, green‐herbal, and cheesy notes based on ester compounds, alcohol and branched‐chain acids production although, the production of propanoic acid by W. anomalus increased the cheesy character in the sauces. CONCLUSION The aroma profile of fermented chilli pepper sauces depends not only on the chili pepper varieties used but also on the fermentation process as a source of aroma compounds. The use of probiotic yeast can be used to improve and diversify the aroma profile of fermented chilli pepper sauces. © 2020 Society of Chemical Industry